Peningkatan Kesadaran dan Keterampilan Warga dalam Pengelolaan Sampah Rumah Tangga Berbasis 3R - Susanti, Nila (Yayasan Literasi Altruis Khatulistiwa, 2025)
Waste management in rural areas is often not handled optimally due to the low level of community awareness and skills. Household waste that is disposed of carelessly not only causes environmental pollution but also disrupts village aesthetics and poses health risks. This community service program aimed to improve the knowledge, skills, and participation of residents in Kalianyar Village, Kapas District, Bojonegoro Regency in household waste management based on the 3R principles (Reduce, Reuse, Recycle) using the Participatory Action Research (PAR) method. The program was carried out through four main stages: (1) problem identification with residents and mapping of waste sources; (2) planning through education, training, and the establishment of a waste management institution; (3) action in the form of socialization, training on separating organic and inorganic waste, compost production using the Takakura basket method and biopore holes, as well as processing inorganic waste into handicrafts; and (4) reflection and evaluation to measure the success of the program. The results indicated an increase in residents’ knowledge from an average of 55% to 85%. As many as 70% of participants began practicing waste separation at home, 50% produced compost independently, and 35% utilized inorganic waste into creative products with economic value. In addition, a Village Waste Bank was established and successfully collected 120 kg of inorganic waste within the first two weeks of operation. These findings demonstrate that the PAR method is effective in building collective awareness and strengthening community engagement in maintaining environmental cleanliness. The success of this program is expected to serve as a replication model for other villages in realizing a clean, healthy, and sustainable environment.